牦牛脂肪不同脱腥处理比较及其腥味物质分析Comparison of different deodorization methods for yak fat and its fishy odor substances analysis - 周佳，徐瑾，赵文俊，张丽，韩广兴，韩玲，余群力ZHOU Jia， XU Jin， ZHAO Wenjun， ZHANG Li， HAN Guangxing， HAN Ling， YU Qunli (Zhongguo youzhi)
旨在提高牦牛脂肪的综合利用，以新鲜的牦牛脂肪为原料，分别采用酵母葡聚糖、活性干酵母、β-环糊精、茶多酚对牦牛脂肪进行脱腥处理，以牦牛脂肪所炼制的牦牛油腥味值作为评价指标，采用单因素实验优化4种脱腥方法的条件，并采用顶空固相微萃取-气相色谱-质谱联用(HS-SPME-GC-MS)技术对脱腥处理前后牦牛脂肪所炼制的牦牛油的挥发性风味物质组成及含量进行分析，采用相对气味活度值（ROAV）确定牦牛脂肪可能的腥味物质，并对脱腥处理前后牦牛油进行感官评价。结果表明：4种脱腥方法的最佳条件为酵母葡聚糖质量分数1.2%、料液比1∶ 4、浸泡时间2 h，活性干酵母质量分数1.1%、料液比1∶ 4、浸泡时间40 min，β-环糊精质量分数0.6%、料液比1∶ 4、浸泡时间40 min，茶多酚质量分数0.35%、料液比1∶ 3、浸泡时间50 min；经酵母葡聚糖、活性干酵母、β-环糊精、茶多酚脱腥处理的牦牛油中分别检出63、61、68、65种挥发性风味物质，其中可能的腥味物质含量较未脱腥处理的降低，这些腥味物质可能是（E）-2-辛烯醛、1-辛烯-3-醇、正己酸、庚酸、辛酸、油酸等；经挥发性物质分析和感官评价综合判定，酵母葡聚糖处理对牦牛脂肪的脱腥效果最佳。综上，酵母葡聚糖、 β-环糊精、活性干酵母、茶多酚溶液浸泡处理可降低牦牛脂肪的腥味物质含量，其中以酵母葡聚糖的脱腥效果最佳。In order to improve the comprehensive utilization of yak fat, the deodorization of yak fat was carried out with fresh yak fat as raw material by using yeast glucan, active dry yeast, β-cyclodextrin and tea polyphenol, respectively. The fishy odor value of yak oil prepared from yak fat was used as the evaluation index, and the deodorization conditions for the four deodorization methods were optimized by single factor experiment. Headspace solid-phase microextraction-gas chromatography-mass spectrometry (HS-SPME-GC-MS) was used to analyze the composition and content of volatile flavor substances of yak oil produced from yak fat before and after deodorization, the relative odor activity value (ROAV) was used to analyze the possible fishy odor substances, and the sensory properties of yak oil before and after deodorization were compared. The results showed that the optimal conditions for the four deodorization methods were yeast glucan mass fraction of 1.2%, material-liquid ratio of 1∶ 4, and soaking time of 2 h for yeast glucan deodorization; active dry yeast mass fraction of 1.1%, material-liquid ratio of 1∶ 4, soaking time of 40 min for active dry yeast deodorization;β-cyclodextrin mass fraction of 0.6%, material-liquid ratio of 1∶ 4, soaking time of 40 min for β-cyclodextrin deodorization; tea polyphenol mass fraction of 0.35%, material-liquid ratio of 1∶ 3, soaking time of 50 min for tea polyphenol deodorization. There were 63, 61, 68 and 65 volatile flavor substances in yak oil deodorized with yeast glucan, active dry yeast, β-cyclodextrin, and tea polyphenol, respectively, in which the contents of possible fishy odor substances were reduced compared with undeodorized yak fat. The fishy odor substances of yak fat could be (E)-2-octenal, 1-octen-3-ol, n-hexanoic acid, heptanoic acid, caprylic acid, oleic acid and so on. The yeast glucan treatment had the best deodorization effect on yak fat, as determined by the combination of volatile substance analysis and sensory evaluation. In conclusion, yeast glucan, β-cyclodextrin, active dry yeast, and tea polyphenol solution soaking treatment can reduce the content of fishy odor substances in yak fat, and among them, the deodorization effect of yeast glucan is the best.